Density studies of 1, 8-diazabicyclo[5.4.0]undec-7-ene (DBU)-glycerol and CO2-DBU-glycerol solutions at temperatures between 288.15 K and 328.15 K. (August 2018) - Lin, Si; Lu, Houfang; Liu, Yingying; Liu, Changjun; Liang, Bin; Wu, Kejing
Highlights: The density of CO2 unloaded and loaded DBU-glycerol solution were measured over the whole composition. Four models were compared to correlate and predict the density of DBU-glycerol systems. A new model-modified proportionality method of CO2 -loaded DBU-glycerol mixtures is put forward. The modified proportionality method proposed in this paper is superior to the proportionality model previously reported. Abstract: The binary system of glycerol and 1, 8-diazabicyclo[5.4.0]undec-7-ene (DBU) possesses promising potential for CO2 absorption, and critical physical properties, especially density, analysis are important for its application. In this work, density of DBU-glycerol system before and after CO2 absorption at temperatures between 288.15 K and 328.15 K was studied by the pycnometer method. In DBU-glycerol system, the density decreases with increases in both temperature and DBU concentration. Excess molar volumes ( V E ) of DBU-glycerol system are negative in the entire composition range and are well correlated with Redlich-Kister equation. Four different models are successfully adopted for correlating and predicting the densities of DBU-glycerol binary solutions. In CO2 -DBU-glycerol system, densities are 0–6% higher than that in the DBU-glycerol system when the mass content of CO2 ( ω CO2 ) based on the total mass of DBU and glycerol is less than 8%. Two different models were set up to correlate the densities with the mole fraction of DBU, temperatures, and CO2 -loadings. The Jouyban-Acree method and the proposed modified proportionality method are preferred respectively for calculating the densities of the CO2 -unloaded and CO2 -loaded DBU-glycerol mixtures due to their simplicity and precision. The density data are useful in the engineering design for CO2 capture using DBU-glycerol solvent.